Stereoelectroencephalography in pre-surgical evaluation of patients with drug-resistant focal epilepsy - A. S. Balatskaya; N. V. Pedyash; A. L. Golovteev; N. A. Kalybaeva; N. P. Utyashev; M. A. Odeniyazova; O. Yu. Bronov; A. A. Zuev (Эпилепсия и пароксизмальные состояния)
Background. Surgical treatment has shown its effectiveness for patients with drug-resistant focal epilepsy: resection or disconnection of the epileptogenic zone leads to relief from epileptic seizures. However, in some cases non-invasive examination may not be sufficient for localization of epileptogenic zone boundaries. Hence, such patients undergo invasive encephalography (EEG) to clarify zone location accounting for seizure development.Objective: to evaluate effectiveness of invasive stereo-EEG in the diagnostics of drug-resistant focal epilepsy.Material and methods. The data collected from 65 patients who underwent stereo-EEG during pre-surgical examination for pharmacoresistant focal epilepsy were retrospectively analyzed within the period of 2016–2019. According to the results of magnetic resonance imaging (MRI), 34 patients had MRI-negative forms of epilepsy, and 31 patients had MRI-positive forms with multiple structural changes in the brain or discrepancies between electro-clinical data and MRI findings.Results. Based on the information obtained by stereo-EEG, 49 patients (75.4%) underwent resection operations. In 16 (24.6%) cases surgical treatment was not carried out due to detected bilateral epileptogenic zone, the lack of convincing data on its location or detecting an epileptogenic zone in a functionally significant region. In 44 operated patients, the follow-up comprised more than 12 months; it was not possible to contact 5 patients. Engel outcomes: I class – 27 (61.3%) patients, II class – 7 (15.9%), III class – 4 (9.1%), IV class – 6 (13.6%). As a result of stereo-EEG, hemorrhagic complications developed in 2 (3.1%) patients: epidural hematoma in 1 case (1.5%), and intracerebral hematoma in 1 case (1.5%). No persistent neurological deficit was noted during continued monitoring.Conclusion. The method of stereo-EEG is effective for determining the epileptogenic zone boundaries in patients with drug- resistant focal epilepsy.